Dynamic Output Feedback Control for Nonlinear Networked Control Systems with Random Packet Dropout and Random Delay. (25th November 2013) - Yu, Shuiqing; Li, Junmin; Tang, Yingde
Abstract : This paper investigates the dynamic output feedback control for nonlinear networked control systems with both random packet dropout and random delay. Random packet dropout and random delay are modeled as two independent random variables. An observer-based dynamic output feedback controller is designed based upon the Lyapunov theory. The quantitative relationship of the dropout rate, transition probability matrix, and nonlinear level is derived by solving a set of linear matrix inequalities. Finally, an example is presented to illustrate the effectiveness of the proposed method.